Identification and characterization of a new pathologic mutation in a large Leber hereditary optic neuropathy pedigree - Sonia Emperador; Mouna Habbane; Ester López-Gallardo; Alejandro del Rio; Laura Llobet; Javier Mateo; Ana María Sanz-López; María José Fernández-García; Hortensia Sánchez-Tocino; Sol Benbunan-Ferreiro; María Calabuig-Goena; Carlos Narvaez-Palazón; et al. (Orphanet Journal of Rare Diseases, 2024)
Abstract Background Most patients suffering from Leber hereditary optic neuropathy carry one of the three classic pathologic mutations, but not all individuals with these genetic alterations develop the disease. There are different risk factors that modify the penetrance of these mutations. The remaining patients carry one of a set of very rare genetic variants and, it appears that, some of the risk factors that modify the penetrance of the classical pathologic mutations may also affect the phenotype of these other rare mutations. Results We describe a large family including 95 maternally related individuals, showing 30 patients with Leber hereditary optic neuropathy. The mutation responsible for the phenotype is a novel transition, m.3734A > G, in the mitochondrial gene encoding the ND1 subunit of respiratory complex I. Molecular-genetic, biochemical and cellular studies corroborate the pathogenicity of this genetic change. Conclusions With the study of this family, we confirm that, also for this very rare mutation, sex and age are important factors modifying penetrance. Moreover, this pedigree offers an excellent opportunity to search for other genetic or environmental factors that additionally contribute to modify penetrance.